2009
DOI: 10.1177/147470490900700409
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Food Preferences of Hadza Hunter-Gatherers

Abstract: Food preferences are important for understanding foraging choices. In studying human foragers rather than other animals, we have the advantage of being able to ask them which foods they prefer. Yet surprisingly, no studies of systematically collected data exist on human forager food preferences. The Hadza of Tanzania are full-time foragers in an area where the hominin record extends back to 3-4 million years ago, so their diet is very relevant for understanding the paleo-diet. Here, we report on their food pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 48 publications
3
37
0
2
Order By: Relevance
“…In conclusion, the "take home message" extrapolated from this systematic review, in strong accordance with other recent studies (Berbesque, 2009;Marino et al, 2011), is to stress the importance of considering a gender specific approach, both in terms of behaviour and of physiology, when addressing nutrition issues in research and in policy making. As a matter of fact, a more detailed informative basis would help the formulation of suitable monitoring programs in the research side, and an increasing effectiveness of policy interventions in respect of different population groups.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…In conclusion, the "take home message" extrapolated from this systematic review, in strong accordance with other recent studies (Berbesque, 2009;Marino et al, 2011), is to stress the importance of considering a gender specific approach, both in terms of behaviour and of physiology, when addressing nutrition issues in research and in policy making. As a matter of fact, a more detailed informative basis would help the formulation of suitable monitoring programs in the research side, and an increasing effectiveness of policy interventions in respect of different population groups.…”
Section: Discussionsupporting
confidence: 50%
“…The results of a study conducted on the Hazda, a tribe of human foragers living in Tanzania, also showed a sex differences in food preferences, with males preferring meat more and females preferring berries more (Berbesque, 2009). Overall, the most relevant differences according to gender in food choices in modern western societies, emerging from our literature review, were in the relationship between eating habits and health consciousness, and between eating behaviour and weight control.…”
Section: Key Determinants In Food Choice: a Gender Perspectivementioning
confidence: 84%
See 1 more Smart Citation
“…Three findings support the view that a physiological sex difference affects sweet preference in anthropoid primates: 1) Among the Hadza of Tanzania, hunter-gatherers who derive Ͼ90% of their energy from wild food, although honey was the most preferred food in both sexes, women preferred sweet berries more than meat, whereas men preferred meat more than berries (61). 2) A field study of wild Borneo orangutans (Pongo pygmaeus) indicated that when sweet fruits were in season, males increased their intake about twofold (from 3,800 to 8,400 kcal/day), whereas females increased their intake about four-fold (from 1,800 to 7,400 kcal/day) (401).…”
Section: Sex Differences In Eating In Anthropoid Primatessupporting
confidence: 53%
“…Nutritionally, honey contributes an important percentage of calories to the Hadza diet, and fondness of honey among the Hadza represents an important aspect of their relationship to the baobab tree. In their recent study, Berbesque and Marlowe (2009) document the Hadza ranking of their staple foods. They report both men and women ranked honey as number one and baobab as number two, but they differed on the relative position of meat and berries.…”
Section: A B Cmentioning
confidence: 99%